If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7u + -2u = 3u Combine like terms: 7u + -2u = 5u 5u = 3u Solving 5u = 3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3u' to each side of the equation. 5u + -3u = 3u + -3u Combine like terms: 5u + -3u = 2u 2u = 3u + -3u Combine like terms: 3u + -3u = 0 2u = 0 Divide each side by '2'. u = 0 Simplifying u = 0
| 1=4x+3*(5/3)-(2/3x) | | 25-4/10x | | 3y=5-2x | | x/5-3=10 | | 7x+8=5x-12 | | 1=4x+3y | | -m^2-17*m=0 | | 6x-x=60 | | -5*0=-4*4+16 | | 9u^(-4/5)=1 | | 8p-40-2p=50 | | 3*4=y+12 | | 4t+4=-21+11t | | 4+20=20 | | 2x^2-8x-42/6x^2 | | 3x^2+24x+144=0 | | 3x-2.5=7 | | -2*n+7*n-1=0 | | 8m+10-5m=34 | | 4*g^2-12*g+11=0 | | 30/5.9=k/10 | | 3m-6=8m | | 7/3=52/u | | 3x=-3.2+0.8x+12 | | 5y^(-4/3)=1 | | m/25=16/98 | | -2x+1=2(x-4) | | 3f-80+25+10k= | | 2/s=3/18 | | 3G+50+2g=125 | | 7/5(-35)+11 | | 5w^(-1/3)=3 |